Oral Microbiota and Inflammatory Bowel Diseases: Detection of Emerging Fungal Pathogens and Herpesvirus - Manoel Marques Evangelista Oliveira; Letícia Bomfim Campos; Fernanda Brito; Flavia Martinez de Carvalho; Geraldo Oliveira Silva-Junior; Gisela Lara da Costa; Tatiane Nobre Pinto; Rafaela Moraes Pereira de Sousa; Rodrigo Miranda; Rodolfo Castro; Cyrla Zaltman; Vanessa Salete de Paula (Biomedicines)
Background/Objectives: Ulcerative colitis (UC) and Crohn’s disease (CD) are the usual clinical forms of inflammatory bowel disease (IBD). Changes in the oral microbiota, especially the presence of emerging fungi and herpesviruses, have been shown to worsen the clinical aspects of IBD. The aim of this study was to screen for emerging pathogens in the oral yeast microbiota and the presence of herpesvirus in IBD patients. Methods: Oral swabs of seven UC or CD patients were collected. The samples were plated on Sabouraud Dextrose Agar and subcultured on CHROMagar Candida and CHROMagar Candida Plus. Polyphasic taxonomy was applied and identified using molecular tools, such as MALDI-TOF MS and ITS partial sequencing. Multiplex qPCR was used to identify the herpesvirus. Results: The mean age was 38.67 ± 14.06 years, 57.14% were female, and two had diabetes. The CD patients presented with Rhodotorula mucilaginosa, Candida orthopsilosis and Kodamaea jinghongensis, while the UC patients presented with Cutaneotrichosporon dermatis, Candida glabrata, Candida lusitanea and Candida tropicalis. Two UC individuals had at least one herpesvirus. In the first individual, a co-detection of Herpes Simplex Virus 1 (HSV-1) and C. lusitaniae was observed. The second presented with co-infections of Epstein–Barr virus (EBV), Human Herpesvirus 7 (HHV-7) and C. tropicalis. Conclusions: We identified rarely described yeasts and co-infections in IBD patients, highlighting the need to identify emerging pathogens in the oral microbiota, as they may contribute to opportunistic infections.